A Facile and Efficient Ni-N-C Electrocatalyst Derived from Superabsorbent Resin for Oxygen Evolution Reaction. Issue 4 (27th April 2021) - Yin, Yawen; Liao, Songyi; Lin, Hai; Liu, Fang; Liu, Yidong; Xiao, Yinguo; Min, Yong
Abstract : The electrocatalysts for oxygen evolution reaction (OER) with efficiency and low-cost have become a critical subject for renewable energy technology. Owing to excellent catalytic activity, the inexpensive M–N–C (M = metal) catalysts are generally considered as the promising electroactive materials for the OER. Recently, research has led to great progress in the performance of M–N–C electrocatalysts. However, the large-scale commercial application of M–N–C catalysts is still limited by their complicated preparation process. Herein, we introduce a facile and efficient Ni-N-C electrocatalyst derived from superabsorbent resin. Benefiting from the strong coupling between the Ni and highly electronegative O and N elements for more available active sites, as well as from a large increase in defects that improve the electronic transmission, the optimized Ni–N–C catalyst exhibits excellent OER catalytic performance, including current densities of 10 mA cm −2 at an ultra-small overpotential of 214 mV and 20 mA cm −2 at 245 mV, a low Tafel slope (48 mV dec −1 ), and good stability. Compared with the commercial RuO2 catalyst, the Ni–N–C catalyst developed in this work exhibits good catalytic performance with greatly reduced cost. This work may provide a potential solution for Ni–N–C as an excellent OER catalyst in large-scale industrial water-splitting.